Synthesis and Characterization of Iron(III)-Benzoin Complex - EL-AJAILY, M.M.; MAIHUB, A.A.; ABUZWIDA, M.A.; ABOU-KRISHA, M.M.; AMAR, A.A.; ASAIH, E.A. (Asian Journal of Chemistry, 2010)
Benzoin can form complexes with iron(m) in different ratios depending on the number of ligand moles used. The new metal complex of the formula [FeB(OH)2(H2O)2]·6H2O, in which B represents benzoin moiety, has been prepared and characterized by elemental analysis, infrared, electronic spectra and molar conductance. The elemental analysis data show the formatiom of 1 : 1 [M : L] ratio. Infrared spectral data confirm bonding through oxygen of the carbonyl and hydroxyl groups in benzoin. Electronic spectral data support the geometrical structure of the complex being an octahedral structure. The molar conductance measurement indicates the formation of non-electrolytic complex.